Exploring students - Yusuf, Faidah; Ali, Ameer (Universitas Islam Negeri Palangka Raya, Indonesia, 2023)
Students' self-confidence in speaking English remains low. Many students are still embarrassed to speak English since teachers use outdated teaching methods. This study aims to explore students' perspectives on using live-streaming projects on the Facebook group in EFL classes. This study involved forty English Department students at a university in Makassar, Indonesia. They engaged in the live streaming project-based learning (PBL) using the Facebook group in language learning in English classes. Four participants from the four groups consisting of ten participants were selected through random sampling and agreed to participate in a semi-structured interview. The qualitative data obtained from the interview were analyzed through a thematic analysis. Results show that live streaming on the Facebook group as PBL facilitated and increased the students